Supply Chain Management in Smart Cities: Ensuring Sustainability through Flexibility in Thailand - Khajornsak Thaiprayoon; Aksorn Sawasdee; Kittisak Jermsittiparsert (International Journal of Supply Chain Management, 2019)
The story which was started with the concept of carbon free city has now obtained its maturity with the new need for smart cities. Life of such smart cities can only get oxygen from efficient supply chain practices from business point of view. Because the end outcome of such smart cities is to achieve sustainability. This research is based on supply chains of manufacturing units located in smart cities that how different practices like instrumental, interconnected and intelligent supply chain have their impact on sustainability performance in mediating role of supply chain flexibility. Respondents were sampled from manufacturing industry of Thailand and especially those firms which were located in such cities which have aimed to become smart cities in next five years. Middle-level management was surveyed through questionnaire and data was then analyzed on SPSS and AMOS. All dimensions or practices of smart city supply chain found positively related with sustainability performance and results also flagged significant positive mediating role of supply chain flexibility in respective relationships. This study’s originality can be found in inclusion of supply chain flexibility as mediator which also has implications for industry and literature.